Prognosis of colorectal cancer with liver metastasis: value of a prognostic index - Wang,Y. (2010)
The objective of the present study was to explore the factors related to the prognosis of colorectal cancer (CRC) and to establish a prognostic model for the selection of patients who might benefit from hepatic resection for metastatic CRC. A total of 293 patients undergoing liver resection for metastatic CRC (172 males and 80 females ranging in age from 26 to 80 years) were selected and clinical, pathological and outcome data were examined in this retrospective study. The prognostic index (PI) of the patients was calculated on the basis of results of multivariate analysis. Patients were stratified into different groups, with survival curves projected according to PI. The 1-, 3-, and 5-year overall survival rates were 58.3, 26.4, and 11.3%, respectively. Univariate analysis indicated that degree of primary tumor differentiation, resection margin, preoperative carcinoembryonic antigen (CEA) level, number of liver metastases, and resection of liver metastases were associated with prognosis (P < 0.05). In multivariate analysis, the last three factors were found to be independent prognostic factors. The resection of liver metastases was a favorable factor. Patients were classified into three groups according to PI, which differed significantly in survival rate (P < 0.05). The individual survival rate was evaluated based on PI. Resection of hepatic colorectal metastases may produce long-term survival and cure. The proposed PI was easy to use, was highly predictive of patient outcome, and permitted categorization of patients into treatment groups.